Evaluating Legal Handling of Child Sexual Abuse Cases: A Model from the Enrekang District Attorney's Office through an Islamic Education Lens - Lewang, Sunarti; Hanafie Das, St. Wardah; Hamang, M. Nasri; Hamang, Rayamangsi (Al-Ulum, 2025)
This study examines the handling of child sexual abuse cases at the Enrekang District Attorney's Office from the perspective of Islamic education. Using a qualitative approach, data is collected through in-depth interviews, observations, and documentation to evaluate the effectiveness of law enforcement. The results of the study show that the handling of the case has been in accordance with the applicable legal provisions and procedures, but still faces obstacles in proof, especially when the perpetrator has a close relationship with the victim or limited physical evidence. Islamic religious education plays an important role as a preventive effort through strengthening moral values and collective responsibility from an early age, which requires the involvement of families, communities, schools, law enforcement officials, and local governments. This study emphasizes the need for periodic evaluations to strengthen inter-institutional coordination, monitor victims' psychological recovery, and assess the effectiveness of family, school, and community-based prevention.